2008
DOI: 10.1007/s10800-008-9682-4
|View full text |Cite
|
Sign up to set email alerts
|

Thin film YSZ coatings on functionally graded freeze cast NiO/YSZ SOFC anode supports

Abstract: Intermediate temperature (600-800°C) solid oxide fuel cell (SOFC) technology is often limited by inadequate gas transport in electrodes, and high ion transport resistance electrolytes. In this study, large area filtered arc deposition (LAFAD) and hybrid filtered arc-assisted e-beam physical vapor deposition (FA-EBPVD) technologies, in combination with freeze-tape-casting, were used to fabricate SOFC anode/electrolyte bi-layers with functionally graded porous anode microstructures and thin film electrolytes fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…The YSZ grain dimension was calculated with a mean 50 nm and standard deviation close at 9 nm, other research work as reference 8 report for a calcination near to 1000 °C, with sol-gel technique a size between 30 and 40 nm, but they do not say their heating speed, neither their time inside the four, the reference 10 reported for YSZ thin film with laser technique a grain size 21.4± 1.4 nm. This YSZ material in their commercial manner (TZ8YS, Tosoh) has reported between 20 and 30 nm [1,11]. The grain size of this study by image analysis is close to the reported values and the YSZ commercial powder is possible that it will be grinding in order to get a more little grain size.…”
Section: Ysz Materials Microstructure By Scanning Electronic Microscopsupporting
confidence: 82%
“…The YSZ grain dimension was calculated with a mean 50 nm and standard deviation close at 9 nm, other research work as reference 8 report for a calcination near to 1000 °C, with sol-gel technique a size between 30 and 40 nm, but they do not say their heating speed, neither their time inside the four, the reference 10 reported for YSZ thin film with laser technique a grain size 21.4± 1.4 nm. This YSZ material in their commercial manner (TZ8YS, Tosoh) has reported between 20 and 30 nm [1,11]. The grain size of this study by image analysis is close to the reported values and the YSZ commercial powder is possible that it will be grinding in order to get a more little grain size.…”
Section: Ysz Materials Microstructure By Scanning Electronic Microscopsupporting
confidence: 82%
“…14 The LSM and YSZ powders were first ballmilled dry to form a homogenous powder. This mixture was slowly added into deionized (DI) water containing an ammonium polymethacrylate dispersant (Darvan C-N, R.T. Vanderbilt Co., Norwalk, CT) until approximately 25 vol.% solids was reached.…”
Section: Preliminary Aqueous Co-dispersion Studiesmentioning
confidence: 99%
“…The large number density of ceramic bridges and secondary pores within the alcohol samples believed to result from interactions between alcohols, particularly methanol, may be extremely beneficial in increasing TPB area, but, especially within the methanol sample which had increased tortuosity along the freezing direction, they may hinder gas flow compared to the pore structure of the control sample. 20 Other methods of increasing TPB area without significantly increasing tortuosity include incorporating a second sacrificial phase or by partial sintering to achieve submicron porosity, as it is not achievable in freeze-cast structures. 37,43 Alternatively, SOFCs can be improved by modifying the electrode pore surface through infiltration of particles.…”
Section: Accepted Articlementioning
confidence: 99%